Dietary resveratrol alleviates liver and intestinal injury in ducks under cage rearing system - Yong Tian; Xiangshan Liu; Li Chen; Tao Zeng; Tiantian Gu; Wenwu Xu; Jindong Ren; Lizhi Lu (Poultry Science)
Cage rearing is a promising farming method. However, our previous studies have demonstrated that changes in farming practices induce oxidative stress and inflammation in the liver and duodenum of ducks. Resveratrol (RES), a natural plant polyphenol, possesses antioxidant, anti-inflammatory, and cytoprotective properties. This study evaluated the alleviating effects of RES against cage-rearing-induced duck health problems, emphasizing the involvement of redox imbalance, inflammatory response, endoplasmic reticulum (ER) stress, apoptosis, and PI3K/AKT and MAPK/ERK pathways. A total of 120 healthy 12-week-old female ducks were transferred to a cage system and randomly assigned to two dietary RES groups with 6 replicates each (10 ducks per replicate), including basal diet + 0 mg/kg RES (control group, CON), and basal diet + 500 mg/kg RES (RES-treated group, RES). During the early stages (within 10 days) of cage rearing, blood, liver, and duodenal samples were collected for analysis. The results demonstrated that RES reduced histopathological damage in the liver and duodenum of cage-reared ducks. It also reduced serum albumin levels, increased serum aspartate aminotransferase and alanine aminotransferase levels, and enhanced antioxidant (increased CAT, GSH-Px, SOD, and T-AOC activities in the serum, liver, and duodenum, and reduced the increase in MDA) and anti-inflammatory properties (reduced pro-inflammatory cytokines interleukin (IL)-1β and IL-6 secretion and increased anti-inflammatory cytokine IL-4 levels). Additionally, quantitative real-time polymerase chain reaction revealed that RES intervention reversed the abnormal mRNA abundance of biomarkers associated with inflammatory injury (iNOS and COX2) in the liver, and ER stress (GRP78) and apoptosis (Bax and Bcl2) in the liver and duodenum of cage-reared ducks. Further analysis of key proteins in the PI3K/AKT and ERK MAPK signaling pathways revealed that RES promoted AKT phosphorylation in the liver and duodenum of cage-reared ducks and reduced cleaved caspase-3 protein content. Overall, RES prevents cage-rearing stimuli-induced liver and intestinal injury in ducks by enhancing liver function, improving antioxidant properties, inhibiting inflammation, ER stress, and apoptosis, and activating the PI3K/AKT signaling pathway.